Symptom monitoring in cancer and fully automated advice on supportive care: Patients' perspectives on self‐management strategies and the eHealth self‐management application Oncokompas. (2nd August 2021) - Schuit, Anouk S.; van Zwieten, Valesca; Holtmaat, Karen; Cuijpers, Pim; Eerenstein, Simone E. J.; Leemans, C. René; Vergeer, Marije R.; Voortman, Jens; Karagozoglu, Hakki; van Weert, Stijn; Korte, Mira; Frambach, Ruud; et al.
Abstract: Objective: The web‐based application Oncokompas was developed to support cancer patients to self‐manage their symptoms. This qualitative study was conducted to obtain insight in patients' self‐management strategies to cope with cancer and their experiences with Oncokompas as a fully automated behavioural intervention technology. Methods: Data were collected from semi‐structured interviews with 22 participants (10 head and neck cancer survivors and 12 incurably ill patients). Interview questions were about self‐management strategies and experiences with Oncokompas. Interviews were audio‐recorded, transcribed verbatim and analysed using thematic analysis. Results: Participants applied several self‐management strategies, among which trying to stay in control and make the best of their situation. They described Oncokompas' added value: being able to monitor symptoms and having access to a personal online library. Main reasons for not using Oncokompas were concentration problems, lack of time or having technical issues. Recommendations were made for further development of Oncokompas, relating to its content, technical and functional aspects. Conclusions: Survivors and incurably ill patients use various self‐management strategies to cope with cancer. The objectives of self‐management interventions as Oncokompas correspond well with these strategies: taking a certain responsibility for your well‐being and being in charge of your life as long as possible by obtaining automated information (24/7) on symptoms and tailored supportive care options.